Ibn Kathir’s observations in the criticism of the Sirah’s narrations: نقدِ روایاتِ سیرت میں ابن کثیر ؒکے ملحوظات - Shah, Dr. Sayyed Wali Ullah; Safia, Safia; Ayyub, Muhammad (Al Khadim Research Journal of Islamic Culture and Civilization, 2025)
This study examines Imam Ibn Kathīr’s methodology in Sīrah scholarship, focusing on two key aspects: his sources and references, and his critical evaluation of Sīrah traditions. The research identifies the primary works he directly consulted—such as Ṭabaqāt Ibn Saʿd, Tārīkh al-Umam wa al-Mulūk, and Tārīkh Dimashq—and the secondary sources accessed indirectly. Ibn Kathīr grounded his writings in the Qur’an, authentic ḥadīth, exegetical opinions, and the statements of the salaf, while deliberately avoiding isolated or unreliable reports. His preference was for narrations with strong chains of transmission, comprehensive content, and sound style.In his critical approach, Ibn Kathīr first evaluated reports against the Qur’an and authentic Sunnah, followed by consensus, sound reason, and lived experience. He adopted the principles of reconciliation, abrogation, and preference to resolve apparent contradictions, and highlighted instances of error, textual corruption, or misrepresentation. His stance on Isrā’īliyyāt mirrored that of earlier scholars: acceptance when corroborated by revelation, rejection when contradictory, and conditional citation when neutral.On the conditions of transmission, he required narrators to be Muslim, mature, rational, just, and of upright character, emphasizing detailed criticism over general accreditation. He stressed verbatim transmission, though he allowed bi-l-maʿnā narration for scholars. Regarding innovators (ahl al-bidʿah), Ibn Kathīr upheld the mainstream scholarly position of rejecting the narrations of propagating innovators while cautiously engaging with those of non-propagating ones.Overall, Ibn Kathīr’s methodology reflects a rigorous and balanced approach, marked by a commitment to authenticity, caution against doubtful material, and a systematic framework for assessing Sīrah traditions.